2003
DOI: 10.1111/j.1365-2621.2003.tb05804.x
|View full text |Cite
|
Sign up to set email alerts
|

Lethality of Listeria monocytogenes in Fully Cooked and Vacuum Packaged Chicken Leg Quarters During Steam Pasteurization

Abstract: Fully cooked chicken leg quarters (160 g to 300 g) were injected to contain 10 7 to 10 8 colony-forming units (CFU)/g of a 5-strain Listeria monocytogenes culture. The inoculated leg quarters were vacuum-packaged in 0.08-mm-thick packaging films and then pasteurized at 96°C via steam. The heat transfer coefficient was about 760 W/m 2 K in the steam cooker. Seven log 10 (CFU/g) reduction of L. monocytogenes was achieved in about 22 min of steam treatment. Results from the inoculation tests agreed with the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The z-values of a 5-strain cocktail in duck muscle, turkey breast, and chicken breast were 5.04, 5.29, and 5.71°C, respectively (Murphy et al, 2003b). In chicken leg quarter meat, the z-value of L. monocytogenes was determined as 5.76°C (Murphy et al, 2003a). For a 6-strain cocktail of L. monocytogenes in beef, the z-value of was reported as 6.01°C (Murphy et al, 2004b).…”
Section: Kinetic Analysis Of Survival Curvesmentioning
confidence: 99%
“…The z-values of a 5-strain cocktail in duck muscle, turkey breast, and chicken breast were 5.04, 5.29, and 5.71°C, respectively (Murphy et al, 2003b). In chicken leg quarter meat, the z-value of L. monocytogenes was determined as 5.76°C (Murphy et al, 2003a). For a 6-strain cocktail of L. monocytogenes in beef, the z-value of was reported as 6.01°C (Murphy et al, 2004b).…”
Section: Kinetic Analysis Of Survival Curvesmentioning
confidence: 99%
“…Pasteurization of RTE meats in individual packages is an alternative for some manufacturers since this technology can reduce or even eliminate L. monocytogenes with confidence. A few studies have been reported using either steam or hot water for in‐package pasteurization of cooked chicken breast meats, turkey breast meats, chicken leg quarters, and cooked bologna (Murphy and Berrang 2002; Murphy and others 2003a, 2003b, 2003c, 2005). In general, postlethality in‐package thermal treatment takes a relatively long time (20 to 40 min), and is highly dependent upon the thickness of products.…”
Section: Introductionmentioning
confidence: 99%
“…RTE poultry products can be consumed directly without further cooking and should be free of pathogens. However, even with the most rigorous hygienic operation, fully cooked poultry products might still be exposed to recontamination during subsequent handling and packaging procedures (18,23). To reduce or eliminate the contamination associated with L. monocytogenes, attention has been turned toward postpackage pasteurization procedures (22,24,25).…”
mentioning
confidence: 99%